Advances in Silage Production and Utilization 2016
DOI: 10.5772/64961
|View full text |Cite
|
Sign up to set email alerts
|

Grass Silage for Biogas Production

Abstract: Renewable energy resources of part of the Asian region are not only able to fight against climate change issues but also could contribute to economic growth, employment, and energy safety. Biogas production and use are generally regarded as a sustainable practice that can guarantee high greenhouse gas savings. Thailand is an agricultural area suitable for growing of many plants, especially annual crops that can be used as an energy crop or raw material for biogas plant. In addition, grassland biomass is suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Anaerobic Digestion (AD) is a mechanism or process that transforms and breaks down complex organic matter into biogas (CH 4 and CO 2 ) and some coproducts (solid and liquid co-products) containing oxygen and bacteria. The process will be carried out in four separate phases in total, including hydrolysis, acidogenesis, acetogenesis and methanogenesis (Dussadee et al, 2016).…”
Section: Fundamental Of Anaerobic Digestion Process In Producing Methane Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic Digestion (AD) is a mechanism or process that transforms and breaks down complex organic matter into biogas (CH 4 and CO 2 ) and some coproducts (solid and liquid co-products) containing oxygen and bacteria. The process will be carried out in four separate phases in total, including hydrolysis, acidogenesis, acetogenesis and methanogenesis (Dussadee et al, 2016).…”
Section: Fundamental Of Anaerobic Digestion Process In Producing Methane Gasmentioning
confidence: 99%
“…The reactive fatty acids are converted to more acetic acid, CO 2 , and H 2 S gas by the third stage of acetogenesis. At final stage of methanogenesis, methane gas is being produced by using CO 2 and H 2 S gas (Letinga et al, 1997;Dussadee et al, 2016).…”
Section: Fundamental Of Anaerobic Digestion Process In Producing Methane Gasmentioning
confidence: 99%
“…The worldwide consumption of fossil fuels intensified greenhouse gas emissions released to the atmosphere and all the climate changes promoted by global warming (Dussadee et al, 2014 ; Ramaraj & Dussadee, 2015 ). In this context, biofuels are an emerging alternative to liquid fuels due to their high energy content and significantly less CO 2 emissions associated with their use (Dussadee et al, 2016 ). Bioethanol is a potential alternative fuel due to its properties in comparison with gasoline, such as higher flame speed, higher heats of vaporization, and higher-octane number, which makes it an antiknock fuel, are some of the main reasons to encourage its production (Gavahian et al, 2019 ; Vu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that Napier grass had a higher affinity to be used as feedstock and had comparatively higher efficiency to yield biogas. The study showed that Napier grass possessed a higher content of organic substance which enables it to ferment faster and favor the anaerobic digestion [6]. Sawasdee & Pisutpaisal, conducted a study to determine the feasibility of biogas production from Napier grass.…”
Section: Introductionmentioning
confidence: 99%